Intensive Strategy Resuscitation of Hemorrhagic Shock Patients with Ectopic Pregnancy in the Intensive Care Unit: A Case Report - Liliriawati Ananta Kahar; Wiwi Monika Sari; Reyhan Julio (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Ectopic pregnancy is a health problem in women of reproductive age whose products of conception implant outside the endometrium. Fluid resuscitation and maintenance and adequate treatment in intensive care unit can reduce mortality and morbidity in patients. Case presentation: A 19-year-old woman came to the emergency department of Dr. M. Djamil General Hospital Padang with complaints of pain in the lower abdomen for 8 hours before entering the hospital. Physical examination results and obtained anemic conjunctiva (+)/(+). Check-up result in deep vaginal touch (VT) was obtained portion rocking pain (+). Then inspection culdosynthesis with results (+). The patient was diagnosed with acute abdominal ec suspected ruptured ectopic pregnancy at G2P1A0H1 gravid 8-9 weeks with severe anemia. After undergoing laparotomy, the patient was admitted to the ICU for 2 days. Conclusion: Adequate resuscitation of fluids and blood products and overcoming shock causes are crucial in managing hemorrhagic shock in the intensive care unit.